2010
DOI: 10.3324/haematol.2010.023689
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between Epstein-Barr virus and the immune system: a rationale for adoptive cell therapy of EBV-related disorders

Abstract: The Epstein-Barr virus has evolved a plethora of strategies to evade immune system recognition and to establish latent infection in memory B cells, where the virus resides lifelong without any consequence in the majority of individuals. However, some imbalances in the equilibrium between the inherent virus transforming properties and the host immune system can lead to the development of different tumors, such as lymphoproliferative disorders, Hodgkin's lymphoma, Burkitt's lymphoma, and nasopharyngeal carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 106 publications
(122 reference statements)
0
73
0
4
Order By: Relevance
“…These dysregulated genes suggested that the immune response was silenced in NPC. In addition, NPC is closely associated with persistent Epstein-Barr virus (EBV) infection, which has evolved a plethora of strategies to evade immune system recognition and to establish latent infection in memory B cells (28). Seven downregulated genes, CR2, C3, CLU, CD55, FOXJ1, C4A, and BCL6 were enriched in the B-cell-mediated immunity response.…”
Section: Discussionmentioning
confidence: 99%
“…These dysregulated genes suggested that the immune response was silenced in NPC. In addition, NPC is closely associated with persistent Epstein-Barr virus (EBV) infection, which has evolved a plethora of strategies to evade immune system recognition and to establish latent infection in memory B cells (28). Seven downregulated genes, CR2, C3, CLU, CD55, FOXJ1, C4A, and BCL6 were enriched in the B-cell-mediated immunity response.…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80] Impressive results with very favorable toxicity profiles have also been obtained by prophylactic and preemptive administration of EBVspecific cytotoxic T lymphocytes (CTLs). 81 Despite these results, wide applicability of this approach has been limited due to high costs, the labor-intensive procedure, and availability difficulties. However, new strategies to develop more rapid approaches for generating virusspecific T cells and the introduction of a third-party bank with HLA-typed EBV-specific CTLs might alter the therapeutic landscape of PTLD in the near future.…”
Section: Can We Use Ebv Viral Load For Diagnosis and Prevention Of Ptld?mentioning
confidence: 99%
“…105,106 Due to this strong alloreactive mediated complications, further attempts were made to isolate expanded EBV-specific CTLs. By infusing these CTLs, both autologous (recipient derived PTLD) and allogeneic (isolated from the donor itself or from a bank of partial HLA-matched voluntary donors), promising results were obtained in PTLD patients after SOT, recently reviewed by Merlo et al 107 However, wide applicability has been limited so far because of pronounced labor-intensive procedure and by availability problems.…”
Section: Adoptive Immunotherapymentioning
confidence: 99%